DAMPAK KEKERASAN RUMAH TANGGA TERHADAP GANGGUAN KEDEWASAAN ANAK - Mega Oktavia Simamora; Melani Octaviani Malau; Naomi Juliana Simanjuntak; Putri Jelita Hutasoit; Damayanti Nababan (Pusat Riset dan Inovasi Nasional, 2022)
Domestic violence is any act against a person, especially a woman that results in physical, sexual, psychological misery or suffering, and/or neglect of the household, including threats to commit acts, coercion, or deprivation of liberty against the law within the household. Domestic violence is narrowly defined as an act or threat of violence against someone with whom the perpetrator has a deep relationship. Domestic violence is also closely related to violence against children. While children may not be physically harmed, seeing or hearing their parents being abused can be psychologically devastating. Maturity in Latin verbs is called the term adult or adolescene which means to grow into maturity Adult in Dutch is volwassen which means full and wassen means to grow, so volwassen means that it has fully grown or has finished growing Therefore, adults are individuals who have completed their growth and ready to accept a position in society along with other adults. However, a person's maturity can be disturbed if the child lives in a less harmonious family environment or a broken home, because domestic violence (domestic violence) not only affects the parents but also their children. Because the problem of violence (especially in the household) is a form of crime that abuses and tarnishes human dignity, and should be categorized as a type of crime against the law of humanity.